Regional Differences in Unemployment and the Labor Supply Decision - Harald Badinger; Thomas Url (Austrian Institute of Economic Research (WIFO), 1999)
We present a model that describes the labor supply decision of individuals under transaction costs and job-related amenities. The model indicates that individuals will respond to regional differences in wages net of transaction costs and accept higher jobamenities as compensation for low wages. We use a sample of regional data from Eastern Austria to proof the implications of the model. Controlling for demand side effects we can find that the major determinants of regional differences in unemployment rates are wages differentials between districts, the share of public housing, and the sectoral structure of the district's economy. We can identify regional amenities indirectly by using a spatial filter on regional variables and interpret the regional component of the unemployment rate as unobserved amenities.
Keywords: R23; J22; R12; 330; Labor Supply Decision; Regional Unemployment; Spatial Filtering; Arbeitsangebot; Transaktionskosten; Theorie